DESIGN AND TECHNOLOGICAL APPROACH WHEN FORMING READINESS FOR AUTONOMOUS LEARNING ACTIVITIES - Bukhteeva, Elena; Chernavsky, Mikhail; Vartanova, Lyudmila; Gerasimenko, Ivanovna (Revista Inclusiones, 2019)
Introduction. The need for the formation of students’ readiness for autonomous learning activities is caused by modern trends in the economy such as the rapid change of technology, self-employment of population, and the development of entrepreneurship. A modern specialist needs to possess skills such as knowing how to work with big data, project planning, and the ability to quickly acquire new knowledge and professions. The purpose of the present article is to substantiate the relevance and the possibility of forming students’ readiness for autonomous learning activities in order to create their own educational product based on the skills of goal-setting, goal-fulfillment, selfreflection, and self-management. One of the methodological approaches to the formation of readiness for autonomous learning activities is the design and technological approach. Materials and methods. To carry out the study, the authors used content analysis of psychological and pedagogical research of domestic and foreign authors, methods of assessing the level of readiness of students for autonomous learning activities, as well as tested the developed method of autonomous learning activities formation in students. Results. Autonomous learning activities, as a process, are a form of organization of educational activity, aimed at developing in students the skills of goal-setting and target-fulfillment, self-reflection, and self-management, and as a result, the ability to create their own educational product based on the formed skills. Students experience the greatest difficulties when performing tasks requiring the skills of goal-setting and self-reflection. The authors’ method based on self-monitoring and educational strategies has shown effectiveness when forming readiness for autonomous learning activities. Discussion. The results of the application of the authors’ methodology when forming in students the readiness for autonomous learning activities indicate its effectiveness. The practical significance of the study is provided by the obtained results, which gives grounds for its implementation in the educational process of the university, as well as for further research in this direction.